2013
DOI: 10.3390/ijms140713433
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Functional Characterization of c-Jun NH2-Terminal Kinase from the Mediterranean Species of the Whitefly Bemisia tabaci Complex

Abstract: c-Jun NH2-terminal kinase (JNK) signaling is a highly conserved pathway that controls gene transcription in response to a wide variety of biological and environmental stresses. In this study, a JNK from the invasive Mediterranean (MED) species of the whitefly Bemisia tabaci complex was cloned and characterized. The full-length JNK cDNA of MED consists of 1565 bp, with an 1176 bp open reading frame encoding 392 amino acids. Comparison of JNK amino acid sequences among different species showed that the sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, a previous study reported that LRRK2 is overexpressed in TC, and its expression is a relatively specific marker for TC (19). Additionally, as a highly conserved pathway, the c-Jun N-terminal kinase (JNK) signaling pathway functions crucially in regulating gene expression and intracellular metabolism in life activities, including growth and development, apoptosis and cellular response to external stress (20). Recently, the activation of the JNK signaling pathway was reported to mediate thyroid dysfunction re sulting from thyroid inflammatory responses and polychlorinated biphenyls (21).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a previous study reported that LRRK2 is overexpressed in TC, and its expression is a relatively specific marker for TC (19). Additionally, as a highly conserved pathway, the c-Jun N-terminal kinase (JNK) signaling pathway functions crucially in regulating gene expression and intracellular metabolism in life activities, including growth and development, apoptosis and cellular response to external stress (20). Recently, the activation of the JNK signaling pathway was reported to mediate thyroid dysfunction re sulting from thyroid inflammatory responses and polychlorinated biphenyls (21).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their studies on Bombyx mori revealed an underlying function of MAPKs of initiating and terminating embryonic diapause (Fujiwara et al, 2006). Moreover, it has recently been demonstrated that the JNK and p38 MAPK signaling pathways play significant roles during the responses of Bemisia tabaci to low temperature stresses (Li et al, 2012;Wang et al, 2013). Nevertheless, until now, information about the function of MAPKs in Lepidoptera under various environmental stresses is lacking.…”
Section: Introductionmentioning
confidence: 99%